Peran Keadilan dan Kepercayaan terhadap Kepatuhan Wajib Pajak Usaha Mikro Kecil Menengah - Nadia Fajriana; Gugus Irianto; Wuryan Andayani (Universitas Swadaya Gunung Jati, 2020)
AbstractThis study aims to analyze the correlation between procedural justice, distributive justice, and cognitive-based trust and voluntary compliance by Micro, Small and Medium Enterprises (MSMEs) taxpayers. This study also examnines the role of cognitive-based trust as a moderating variable in the relationship between procedural justice and distributive justice and its impact on voluntary compliance by MSMEs taxpayers. The model for this study was developed from The Psychology of Justice Theory and the Slippery Slope Framework. The population of this study is the MSMEs taxpayers in Malang, Indonesia. The sample in this study were 64 MSMEs taxpayer respondents who completed a questionnaire distributed through the Google Forms platform. The data from questionnaires was processed using the SmartPLS 3.0 statistical tool. The results of the study show that procedural justice, distributive justice, and cognitive-based trust can increase voluntary taxpayer compliance while cognitive-based trust is unable to moderate the relationship between procedural justice and distributive justice on voluntary taxpayer compliance.Keywords: Distributive justice; Procedural justice; Tax compliance; Trust; MSMEs.Abstrak Kajian ini ini memiliki tujuan untuk menganalisis peran dari hubungan keadilan prosedural, keadilan distributif, dan kepercayaan berdasarkan kognitif terhadap kepatuhan sukarela pada wajib pajak Usaha Mikro Kecil Menengah (UMKM). Kajian ini juga menjelaskan peran kepercayaan berdasarkan kognitif sebagai variabel moderator hubungan antara keadilan prosedural dan keadilan distributif terhadap kepatuhan sukarela wajib pajak UMKM. Model dari kajian ini dikembangkan dari The Psychology of Justice Theory dan kerangka kerja Slippery Slope. Populasi dari kajian ini adalah wajib pajak UMKM yang terletak di Kota Malang, Indonesia. Sampel pada kajian ini sejumlah 64 responden wajib pajak UMKM. Kajian ini menggunakan kuesioner yang disebarkan melalui Platform Formulir Google. Data yang telah diperoleh dari penyebaran kuesioner diolah menggunakan alat statistik SmartPLS 3.0. Hasil kajian menunjukkan bahwa keadilan prosedural, keadilan distributif, dan kepercayaan berdasarkan kognitif dapat meningkatkan kepatuhan wajib pajak secara sukarela. Kepercayaan berdasarkan kognitif tidak mampu memoderasi hubungan keadilan prosedural dan keadilan distributif terhadap kepatuhan wajib pajak secara sukarela.Kata Kunci: Keadilan distributive; Keadilan procedural; Kepatuhan pajak; Kepercayaan; UMKM.